INCORPORATING KNOWLEDGE MANAGEMENT IN PROMOTING SUSTAINABLE DEVELOPMENT IN FACILITY MANAGEMENT ORGANIZATIONS: A REVIEW - Muhammad Haziq Md Anuar; Hikmah Kamarudin (International Journal of Accounting, Finance and Business, 2023)
The Sustainable Development Goals (SDGs) include the objective of making cities and human settlements more inclusive, safe, resilient, and sustainable. The success of SDGs is closely related to how the facilities are designed, managed and maintained, involving knowledge and awareness. Hence, the application of knowledge management in the context of sustainability has grown in importance over time. Despite its significance, it is observed that this area is still underexplored. With regard to the facilities management field, there are numerous academic research opportunities pertaining to incorporating knowledge management into facilities management organization. This paper highlights the connection between knowledge management, sustainability and facilities management. Literature from related topics was reviewed in order to have a better understanding of sustainable facilities management and its importance. Incorporating knowledge management skills into the current facilities management practice is beneficial as it promotes sustainability and positively impacts future generations in terms of economic, social and environment sustainability.